THE OCCURRENCE OF SYNCHRONIZED JUMPING CROWD AT SPORTS STADIUMS - Martin Verner (Acta Polytechnica CTU Proceedings, 2017)
Since the age of the Rome Empire, people have been going for fun at the stadiums. Today, important reasons for visiting the stadium are sport games or cultural performances. The text is about occurrence of specific types of behaviour during sport games. The experiment was realized at four different sports stadiums and during three kinds of sports. The worst case of loads for the grandstand is the synchronized jumping of a crowd. This is type of behaviour, which can cause over limit vibration, visitors discomfort on the tribune, in the extreme case collapse of the grandstand. In any country today, the standards or references or math models are not for application of dynamic load to grandstand. Only the British standards are making recommendation how the designer should work with dynamic loads.